EFEKTIVITAS SUMBER PENDAPATAN ASLI DAERAH DALAM MENINGKATKAN KEMANDIRIAN KEUANGAN DAERAH PADA BADAN PENGELOLA PAJAK RETRIBUSI DAERAH KABUPATEN MUSI BANYUASIN - Septariani, Jumania (Fakultas Ekonomi Universitas IBA, 2019)
This study aims to determine the Effectiveness of Local Revenue Sources in Increasing the Regional Financial Independence of Musi Banyuasin Regency at the Regional Levy Tax Management Agency in Musi Banyuasin Regency. The method used in this study is quantitative which is qualified by using primary and secondary data in the form of PAD budget realization reports, that is by analyzing data and information relevant to the problem, using effectiveness ratios and independence ratios in the form of fiscal autonomy ratios and routine capability index ratios. Based on the ratio of effectiveness of Local Revenue (PAD) on average from 2014-2017 to 89 , 48%, stated to be less effective because it is less than the standard, which is 90%. Based on the Independence Ratio seen from the ratio of fiscal autonomy, PAD is realized on an average of 8% with very less criteria, seen from the ratio of routine ability index to the average realized 8% with criteria also very low, which means the Regional Government of Musi Banyuasin Regency depend on funds from the Central Government. Although the level of effectiveness and independence is still lacking or low. However, in total regional income, PAD is quite good in promoting financial independence of the Regional Government of Musi Banyuasin Regency.